Comparative study of methods for the extraction of concentrator photovoltaic module parameters. (1st November 2016) - Fernández, Eduardo F.; Montes-Romero, Jesús; de la Casa, Juan; Rodrigo, Pedro; Almonacid, Florencia
Highlights: The modelling of the current-voltage (IV) curve of concentrator modules is still under discussion. The single exponential model (SEM) is widely used to predict the IV characteristics of solar devices. Different methods to extract the parameters of a concentrator module are studied. The quality of the methods is analysed with long-term outdoor experimental data. The dependence of the SEM model parameters with irradiance is also discussed. Abstract: The modelling and outdoor evaluation of high concentrator photovoltaic (HCPV) systems is complex due to the use of multi-junction solar cells and optical devices. At the same time, the single exponential model (SEM) is widely used for predicting the IV characteristics of PV systems. In this paper, several conventional analytical methods for extracting the five parameters of the SEM model of non-concentrating PV devices are applied and evaluated for the electrical characterization of a HCPV module for the first time. Among the different approaches, three simple analytical methods have been selected with the aim of offering rapid and easy solutions for the characterization of HCPV systems. The selected methods are: the method of Phang et al., the method of Blas et al. and the method of Khan et al. In addition, these methods are compared with a numerical extraction method previously introduced by the authors. Results show that all the methods investigated can be valid for predicting the IV curve of a HCPV module except the method of Khan et al., which tends to underestimate the IV curve and maximum power of the module. The dependence of the extracted SEM model parameters with the input irradiance is also discussed.